Disulfide isomerization reactions in titin immunoglobulin domains enable a mode of protein elasticity - David Giganti (Nature Portfolio, 2018)
Titin regulates myocyte stiffness through uncoiling and unfolding but these two processes cannot fully explain its elasticity. Here, the authors use atomic force microscopy to study the properties of titin disulfide bonds, showing that disulfide isomerization represents a third mode of titin elasticity.